Urban and peri-urban aquaculture as an immediate source of food fish: Perspectives of Dhaka City, Bangladesh - MD. Shahidul Islam; Muhammad Tanvir Hossain Chowdhury; MD. Mokhlesur Rahman; MD. Anwar Hossain (Urban Ecosystems, 2004)

Field measurement and simulation of advance rates for continuous and surge irrigated furrows in Pakistan - Muhammad Latif; Sajid Mahmood (Irrigation and Drainage, 2004)
Field tests were conducted with inflow rates of 1.7–2.4 l s −1 to compare the advance rates both in continuous and surge‐irrigated furrows. The furrows were 149 m long, with 0.2–1.5% slopes. Water applied and rate of water advance were measured during five irrigation events. During the first irrigation, a reduction in applied water volume of 23–60% was observed in surge‐irrigated furrows compared with continuous irrigation. It was further noted during the course of the experiments that the surging effect was more pronounced during the first irrigation than in the subsequent irrigation events. However, it was noted that there would be hardly any benefit of the surge for smaller field lengths of 61 m, which are commonly used in Pakistan and many other developing countries. Results simulated by the SIRMOD model revealed that the water front advance curves matched closely with the observed ones in most surge treatments. The simulated performance efficiencies encourage the use and adaptation of surge irrigation in Pakistan, but more field studies are needed for its verification and for making concrete recommendations for its use in farmers' fields. Copyright © 2004 John Wiley & Sons, Ltd.

Comparative study of Cr(VI) uptake and reduction in industrial effluent by Ochrobactrum intermedium and Brevibacterium sp. - Muhammad Faisal; Shahida Hasnain (Biotechnology Letters, 2004)

Nitrogen transport and transformation in packed soil columns from paddy fields - Hideo Nakasone; Muhammad Akhtar Abbas; Hisao Kuroda (Paddy and Water Environment, 2004)

Multiresolution Wavelet Scale Up of Unstable Miscible Displacements in Flow Through Heterogeneous Porous Media - Fatemeh Ebrahimi; Muhammad Sahimi (Transport in Porous Media, 2004)

Stochastic Goal Programming Model for Optimal Blending of Desalinated Water with Groundwater - Muhammad A. Al-Zahrani; Abid M. Ahmad (Water Resources Management, 2004)

Inoculating wheat seedlings with exopolysaccharide-producing bacteria restricts sodium uptake and stimulates plant growth under salt stress - Muhammad Ashraf; Shahida Hasnain; Odile Berge; Tariq Mahmood (Biology and Fertility of Soils, 2004)

Evolution of Shear-Zone Structure in Undrained Ring-Shear Tests - Muhammad Wafid Agung; Kyoji Sassa; Hiroshi Fukuoka; Gonghui Wang (Landslides, 2004)

Salinity tolerance and growth response of juvenile Oreochromis mossambicus at different salinity levels - Khalid Jamil; Muhammad Shoaib; Faisal Ameer; Hong Lin (Journal of Ocean University of China, 2004)

A Flavanone and Two Phenolic Acids from Chrysanthemum morifolium with Phytotoxic and Insect Growth Regulating Activity - Clifford W. Beninger; Mamdouh M. Abou-Zaid; Adrienne L. E. Kistner; Rebecca H. Hallett; Muhammad J. Iqbal; Bernard Grodzinski; J. Christopher Hall (Journal of Chemical Ecology, 2004)

Regulation of cell cycle proteins by chemokine receptors: A novel pathway in human immunodeficiency virus neuropathogenesis? - Renato Brandimarti; Muhammad Zafrullah Khan; Alessandro Fatatis; Olimpia Meucci (Journal of NeuroVirology, 2004)